Sistem Embedded untuk Pengaturan Pakan lkan Mas Koki berdasarkan Banyaknya JumIah lkan dan Ketinggian Air - Arief Wahyu Wicaksono; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Feeding is one of the important things for fish farming and hobbyist businesses. Currently feeding is generally still dependent on human resources that are manual. Therefore designed tools to feed fish that can work automatically based on the time or schedule of feeding and the amount or amount of feed. Nowadays wireless technology is becoming very popular because of its ability to distribute and disseminate data wirelessly. An important factor in keeping fish in an aquarium is the timeliness of fish feeding. Based on this in this final project project is designed and made a fish feed tool based on the number of fish and water level. Then designed a tool that makes it easy to feed fish based on the number of fish that is automatically in accordance with specified. The components of fish feed scheduling support include making the minimum circuit Arduino Uno system as the brain of this tool which will later be filled with programs using the Java language, RTC (Real Time Clock) as a timer, DC Motor to rotate the spiral wire connected to the place of fish feed . Then the ultrasonic sensor readings are processed using an Arduino uno microcontroller. Tests carried out ultrasonic sensor testing, processing time testing, automatic fish feeding testing and the suitability of the serial data monitor and LCD. In this study it was found that the tool worked well, the functional suitability of the feeding equipment was 90% and the results were successful and smooth.